Bovine papillomavirus E2 repressor mutant displays a high-copy-number phenotype and enhanced transforming activity. - Riese, D J (1990)
The methionine codon at bovine papillomavirus type 1 nucleotide 3091 was mutated to determine whether it may serve as an initiation codon for an E2 transcriptional repressor protein and to determine the role of the repressor in the biological activities of the virus. A series of transient expression experiments with CV1 cells documented that the mutation reduced expression of repressor activity from the viral genome and resulted in increased expression of the E5 transforming gene. Viral genomes containing the mutation displayed enhanced transforming activity in several assays in mouse C127 cells, including focus formation, colony formation in agarose, and tumorigenicity. In transformed cells, the mutant viral DNA was maintained as a plasmid with approximately 500 genomes per cell, whereas the wild-type copy number was approximately 75. These results indicate that the wild-type bovine papillomavirus type 1 genome encodes an E2 repressor protein that moderates the viral transforming activity and allows maintenance of the viral DNA at a relatively low copy number.